PENGARUH PROFITABIITAS, UMUR PERUSAHAN, TIPE PERUSAHAAN DAN KEPMILIKAN MANAJEMEN TERHADAP PENGUNGKAPAN SOSIAL BERDASAR ISO 26000 (Studi Empiris pada Perusahaan Pertambangan dan Keuangan yang Terdaftar di BEI Tahun 2011-2012) - Temmy Deny Saputro; Rahardja Rahardja (Diponegoro Journal of Accounting, 2014)
ISO 26000 is an international standard that gives a direction on disclosure of corporate social performance. ISO 26000 release in 2010, one year later Indonesia has begun to try to apply the international standards. There are 37 items disclosure of 7 core subjects of ISO 26000. This study aimed to investigate the influence of profitability,company age, type of company, and management ownershipon disclosure of corporate social performance based on ISO 26000. Data collection using purposive sampling method Chosen As many as 30 mining companies and 30 financial companies used as a sample. Methods of analysis of this study using multiple regression analysis. The results of this study indicate that the variables that affect the disclosure of corporate sosial performanceis age company. While the variables that do not affect the disclosure of corporate social performance is profitability, company type and management ownership.